Nutritional quality analyses of traditional varieties of rice (Oryza sativa) collected from tribal areas in eastern India - RADHAMANI, JALLI; KHAN, ZEBA; SAHAI, SUMAN; TYAGI, RISHI K (The Indian Journal of Agricultural Sciences, 2015)
Traditional varieties of rice (Oryza sativa L.) having withstood the rigors of time (tolerating both abiotic and biotic stresses) are grown by Indian farmers in rural and tribal parts of India for their subsistence. Seeds of 100 traditional varieties were accessed from the Gene Campaign collection of rice from eastern India and evaluated for nutritional traits (protein, amino acid, starch, amylose and amylopectin) to identify (i) nutritionally superior cultivars for improving livelihood of farmers and tribal communities and (ii) trait-specific donor types which can be used in rice improvement programmes. Seeds of tested cultivars exhibited wide variation for nutritional traits. Higher amylose content (>20%) were recorded in 16% cultivars. Amongst the 100 cultivars tested two cultivars, namely, GC/JH/ 2007/187 and GC/OR/2007/168 were identified with very high values for protein and amylose contents. Amylose content was positively correlated with starch and negatively correlated with amylopectin. Several superior cultivars were identified with better combination of two or more nutritional traits which can be recommended for cultivation by the farmers and tribal communities for their livelihood. Such cultivars can be used as donors in rice crop improvement programme, therefore, also need attention for their long-term conservation in field level seed banks and the National Genebank, for future use.